Карикатуры в альманахе «Зарницы» как наглядность эмигрантской прессы в Турции - Üçgül, Sevinç (Acta Polono-Ruthenica, 2019)
The purpose of the present article is to highlight and analyse the publishing activity and peri-odical press of the “white Russians” in Istanbul on the basis of a description of the certain material – caricatures of the painter V. Khadulin (1883/84–1957) in the “Zarnitsy” almanac published in Constantinople in 1920s.The relevance of the given topic is defined by the place taken by caricatures in the illustrative highlighting of the daily as well as social-political aspects of the emigrants’ life.Painter V.F. Kadulin was successful in demonstrating the information of events, phenomenon, processes and problems of the white emigration in Turkey and, in particular, in İstanbul as well as in Bolshevik Russia through his political and socio-everyday caricatures in a visual satiric image-artis-tic form. In the article, we also give detailed information about the painter himself.